Mobile application for patient monitoring system / Muhammad Aiman Md Zuki - Md Zuki, Muhammad Aiman (2015)
This research was about implementing technology usage in the health care area by using mobile applications in monitoring the patient and notified the doctor which patient they have been assigned. The problem statement was lack of efficiency in terms of performance and time. The medical record was recorded in manual written and consuming time when doctor want to review patient medical record. There were three (3) objectives that need to be achieved which were, to study the business process of the Surgical Ward in Hospital Melaka, to design mobile application architecture using three-layer architecture and to develop mobile application for patient monitoring using Android Programming. This project only focused on the Surgical Ward department of Hospital Melaka. The user of this system was only for the doctor and nurse in the Surgical Ward. This project also focused on developing the mobile application, which was covered for medical record of the patient. On top of that, this mobile application used PHP, Java, and XML language to develop the system. Furthermore, this mobile application used Internet to interact with the online database. The manual based monitoring was the most traditional patient monitoring based system. The computer-based system was invented from paper-based system. The computer-based system was the current patient monitoring system and has been implemented for few hospitals. However, the computer-based system was lack in terms of mobility of the system. The system can access in one place. But the mobile application patient monitoring system was more reliable than computer-based system in terms of mobility and their security. Besides that, monitoring the patient using mobile application also has been introduced to make their work faster and efficiently. There was three (3) aspect has been compared to each other. Those three (3) aspects was interface, mobility and their flow of showing the information. After that, the Iterative Methodology was implemented in this project. The findings of this project were to allocate the system in the Surgical Ward of Hospital Melaka. The constructions of the system begin with defining the architectural design of the system. The analysis was done to make sure the objective stated in Introduction, was achieved. The analysis of this project was seen from aspects their role and their business process. This was to make sure the system running follow the business process. Their business process shows the medical record was very private and confidential. Their content also limited to the nurse and the doctor only. Last but not least, the conclusion and the recommendation of this project was defined.